Pertimbangan Hakim Terhadap Permohonan Wali Izin Jual Tanah Harta Bawaan Istri Untuk Biaya Pendidikan Anak Di Pengadilan Negeri Padang Kelas IA (Studi Penetapan Nomor 292/Pdt.P/2022/PN.Pdg) - Abd. Rahmad; Lidya Lidya (Normative Jurnal Ilmiah Hukum, 2025)
In general, a child is someone who is not yet an adult or unmarried, a child who is under age cannot automatically carry out legal actions. The legal actions of minors are under the authority of the guardian. Article 394 of the Civil Code explains that the Court will only grant permission for the actions of parents or guardians in selling property if the District Court considers it. According to KHI Article 87 Paragraph (1), the property inherited by each husband and wife, property obtained as a gift or inheritance, is under their respective control as long as the parties do not specify otherwise in the marriage agreement. To sell land with the condition that parents act as guardians, you must apply for guardianship and apply for a permit to sell land assets to minor children in the District Court. The formulation of the problem in this research is how the judge considers the guardian's request for permission to sell the wife's inherited land for children's education costs at the Padang Class 1A District Court and what is the juridical analysis of the guardian's request for permission to sell the wife's inherited land for children's education expenses at the Padang District Court Class 1A. The research method used is normative juridical, while the nature of the research is descriptive. Data collection techniques through library research and document study are then processed through editing and coding and analyzed qualitatively. The results of the research can be concluded that the Guardian's Application for Permission to Sell Land belonging to his wife for Children's Education Fees. The Petitioner intends to sell or transfer land rights for the purpose of educating 3 (three) children because the applicant's children are still under age and are not yet competent to carry out actions. the law means that the applicant is appointed as the guardian of the applicant's minor children. The judge's consideration of the guardian's request for permission to sell land belonging to his wife to pay for the child's education must notify and obtain permission from the family of the late Sitti Hutari Mulyani, because the land is the inherited property of the late Sitti Hutari Mulyani, according to the judge who heard the applicant's a quo application must be rejected.